1,3,4, Oxadiazole Compound A3 Provides Robust Protection Against PTZ-Induced Neuroinflammation and Oxidative Stress by Regulating Nrf2-Pathway [Retraction] - Alvi AM; Shah FA; Muhammad AJ; Feng J; Li S (Dove Medical Press, 2022)
Alvi AM, Shah FA, Muhammad AJ, Feng J, Li S. J Inflamm Res. 2021;14:7393–7409. The Editor and Publisher of Journal of Inflammation Research wish to retract the published article. Concerns were raised regarding the alleged duplication of images within the article with those from another article published in Oxidative Medicine and Cellular Longevity, Carveol Attenuates Seizure Severity and Neuroinflammation in Pentylenetetrazole-Kindled Epileptic Rats by Regulating the Nrf2 Signaling Pathway, Alvi et al, 2021 (https://doi.org/10.1155/2021/9966663). Both articles have authors in common. Specifically, Figure 6, panel Cortex, Saline appears to have been duplicated with Figure 5, panel Cortex, Diaz from Alvi et al, 2021. Figure 6, panel Cortex, Diaz+PTZ appears to have been duplicated with Figure 5, panel Cortex, Car-20 from Alvi et al, 2021. Figure 7C, panel Cortex, Diaz+PTZ appears to have been duplicated with Figure 7 (TNF-alpha), panel Cortex, CA1, ATRA+PTZ from Alvi et al, 2021. Figure 7C, panel Cortex, PTZ appears to have been duplicated with Figure 7 (p-NF-κB), panel Cortex, Saline from Alvi et al, 2021. Figure 7C, panel Hippocampus, Diaz+PTZ appears to have been duplicated with Figure 7 (p-NF-κB), panel Cortex, CA1, PTZ from Alvi et al, 2021. Figure 7D, panel Cortex, A3-30+PTZ appears to have been duplicated with Figure 6, panel Cortex, ATRA+PTZ+Car from Alvi et al, 2021. Figure 8D, Cortex, PTZ appears to have been duplicated with Figure 8, panel Cortex, ATRA+PTZ+Car from Alvi et al, 2021. Figure 8D, Hippocampus, ATRA+PTZ+A3 appears to have been duplicated with Figure 8, Hippocampus, CA1, PTZ from Alvi et al, 2021. Figure 8D, Hippocampus, ATRA+PTZ appears to have been duplicated with Figure 8, Hippocampus, CA1, ATRA+PTZ from Alvi et al, 2021. Figure 8E, Cortex, ATRA+PTZ+A3 appears to have been duplicated with Figure 7 (p-NF-κB), Cortex, ATRA+PTZ from Alvi et al, 2021. The authors responded to our queries but were unable to provide a satisfactory explanation for the alleged image duplication. The Editor requested for the article to be retracted and the authors agreed with this decision. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.